A Stochastic D/A Converter Based on a Cellular Automaton Architecture. Issue 2 (1998) - Andreadis, I.; Kokolakis, I.; Gasteratos, A.; Tsalides, Ph.
Abstract : The design and VLSI implementation of a new stochastic D/A converter using the properties of Cellular Automata (CA) is presented in this paper. The converter is implemented using a Double Layer Metal (DLM), 0.7 μm, N-well, CMOS technology process provided by the European Silicon Structures (ES2). Its maximum conversion rate is 6 kHz and it is intended to be used in low-cost applications. Additionally, the proposed approach integrates into digital techniques more easily than other popular building D/A techniques.